Health information on alcoholic beverage containers: has the alcohol industry's pledge in England to improve labelling been met?. (15th October 2015) - Petticrew, Mark; Douglas, Nick; Knai, Cécile; Durand, Mary Alison; Eastmure, Elizabeth; Mays, Nicholas
Abstract: Aims: In the United Kingdom, alcohol warning labels are the subject of a voluntary agreement between industry and government. In 2011, as part of the Public Health Responsibility Deal in England, the industry pledged to ensure that 80% of products would have clear, legible health warning labelling, although an analysis commissioned by Portman found that only 57.1% met best practice. We assessed what proportion of alcohol products now contain the required health warning information, and its clarity and placement. Design: Survey of alcohol labelling data. Setting: United Kingdom. Participants: Analysis of the United Kingdom's 100 top‐selling alcohol brands ( n  = 156 individual products). Measurements: We assessed the product labels in relation to the presence of five labelling elements: information on alcohol units, government consumption guidelines, pregnancy warnings, reference to the Drinkaware website and a responsibility statement. We also assessed the size, colour and placement of text, and the size and colouring of the pregnancy warning logo. Findings: The first three (required) elements were present on 77.6% of products examined. The mean font size of the Chief Medical Officer's (CMO) unit guidelines (usually on the back of the product) was 8.17‐point. The mean size of pregnancy logos was 5.95 mm. The pregnancy logo was on average smaller on wine containers. Conclusions: The UK Public Health Responsibility Deal alcohol labelling pledge has not been fully met. Labelling information frequently falls short of best practice, with font and logos smaller than would be accepted on other products with health effects.